Staff Participation and Public Management Reform : Some International Comparisons - Fairnham, David, Hondeghem, Annie., dan Horton, Sylvia (Palgrave Macmillan, 2005)
This book is about the role of civil servants and their trade unions in the public management reform process. It starts by putting public management reform in its economic, social, cultural and legal contexts. Then, building on neo-institutional and stakeholder theories, the book explores how staff and their representative organisations have influenced the formulation and implementation of public management reforms in 12 OECD countries. This study challenges top-down elite theories that have dominated the existing literature and explains how staff participation practices, both direct and indirect, have impacted on the implementation of reforms in different ways in different countries. The book concludes that variations in staff participation in the reform process depend upon institutional and political factors and the distribution of power in the employment relationship.